ENVIRONMENTAL INTEGRITY: REGENERATIVE MINING IN THE DEMOCRATIC REPUBLIC OF CONGO (Hekima Review, 2024)
The Democratic Republic of Congo (DRC) occupies a central place in the global discourse on ecological transition and technological revolution due to its vast tropical forests and abundance of critical mineral resources. However, the current exploitation of these resources raises significant challenges, such as security issues, environmental degradation, and threats to human health. In this paper, I argue for a regenerative mining model in the DRC that aims to ensure the harmonious development of the country and secure a brighter future for the local populations without compromising environmental integrity.